Нові радіовуглецеві дати для пам'яток Північно-Західного Причорономор'я - Іванова, С.В. (Археологія, 2010)
Публікуються матеріали кургану 4 біля с. Вапнярка в околицях м. Одеса з охованнями доби енеоліту—бронзи і ґрунтового могильника пізнього середньовіччя на території міста, що складають певний інтерес, зокрема через радіокарбонні дати. В 2008 г. Белгород-Тирская экспедиция Института археологии НАН Украины исследовала два памятника в пригородах Одессы: курганную группу у с. Вапнярка Коминтерновского р-на и грунтовый могильник в черте города (жилмассив Совиньон 4), на расстоянии около 1,5 км к востоку от с. Бурлачья Балка Овидиопольского р-на.Могильник у с. Вапнярка из девяти курганов известен в научной литературе с середины XIX в. Исследованы четыре кургана — три скифских и один более древний. Курган 4 был сооружен в энеолите и использовался в бронзовом и раннем железном веке. Высота его 0,2 м, диаметр 20—25 м, сильно распахан. В нем обнаружено 20 погребений: два энеолитические, 15 бронзового века, скифское и два неопределенные. Сооружение первоначальной насыпи кургана связано с погребениями 4 и 9 энеолитической эпохи, их окружал частично сохранившийся кромлех диаметром около 5,6 м. Он был сооружен из небольших, рваных по слою грубо отесанных полигональных плит известняка, частично — из бутового камня различной величины; плиты поставлены орфостатно. Захоронения и кромлех были перекрыты первой насыпью из чернозема с частыми вкраплениями мелкой известняковой крошки. Ее диаметр около 10 м, высота не менее 0,6—0,7 м. Вторая насыпь, края которой фиксировались в бровках, из плотного светло-серого суглинка, диаметр ее около 18,5 м, высота около 1,0 м. Возможно, она имела конструктивный характер. Третья насыпь не восстанавливается из-за сильной распашки кургана. Ее диаметр, вероятно, был не менее 20 м, высота неизвестна. Практически все погребения кургана, за исключением энеолитических, впущены с уровня третьей насыпи. Интерес, в первую очередь, представляют погребения, для которых получены радиоуглеродные даты: энеолитическое (4), ямной культуры (16 и 18), катакомбной (3) и бабинской (6). Грунтовый могильник Совиньон из пяти захоронений был выявлен в результате шурфовки. Все погребения безынвентарны, ориентированы в западном направлении. Судя по результатам радиоуглеродного датирования, могильник относится к золотоордынскому времени и датируется серединой XIV в. Отметим, что грунтовые захоронения кочевников золотоордынского периода не были известны в Северо-Западном Причерноморье вплоть до настоящего времени. Источниковедческую базу составляют исключительно подкурганные захоронения, число которых невелико — около 70. Было лишь одно исключение — погребение у с. Флориновское. In 2008, Bilhorod-Tyras Expedition of the Institute of Archaeology of the National Academy of Sciences of Ukraine was researching two monuments in suburbs of Odesa: group of barrows near Vapnyarka village of Kominternivske Region, and a burial ground within the precincts of the city (Sovinyon 4 housing estate) at a distance approximately 1,5 km to the east from Burlacha Balka village of Ovidiopol Region. The burial ground near Vapnyarka village of 9 barrows is known in the scientific literature since the middle of the 19th c. Four barrows have been studied: three of the Scythian period and a one of more ancient period. Barrow 4 was constructed in the Copper Age and was used in the Bronze and the Early Iron Ages. Its height is 0,2 m, diameter 20—25 m, and it is intensively ploughed up. 20 burials were found there: two of the Copper Age, 15 of the Bronze Age, one of the Scythian period, and two were not defined. Construction of the original embankment of the barrow is related to burials 4 and 9 of the Copper Age, they were surrounded by partly extant cromlech of 5,6 m in diameter. It was constructed of small, broken by the layer, roughly trimmed polygonal limestone plates, partly of rubble of various sizes; plates were put orphostationally. Burials and cromlech were covered by the first mound made of soil with mixture of small limestone bits. It is about 10 m in diameter and of not less than 0,6—0,7 m in height. The second mound, edges of which were fixed in kerbs, was made of light gray plastic clay; it’s 18,5 m in diameter and 1,0 m high. Probably, it had a constructive function. The third mound can not be reconstructed due to intensive ploughing up of the barrow. Its diameter apparently was not less than 20 m and its height is not known. In fact, all burials in the barrow, except for the ones of the Copper Age, were sunk from the level of the third mound. Interest, first of all, represent those burials for which radiocarbon dates have been obtained: the Copper Age (4): Yamna culture (16 and 18), Catacomb (3), and Babynska (6) cultures. The burial ground Sovinyon of five burials was discovered as a result of making prospect holes. All burials are without inventories, oriented to the west. Judging from the results of radiocarbon dating the burial ground belongs to the Golden Horde period and is dated by the middle of the 14th c. It should be noted that ground burials of the nomads of the Golden Horde period were not known in the North-Western coast of the Black Sea up to now. Only under-barrow burials constitute the source study base; there are not many of them, about 70. There was only one exception, a burial near Florinovske village.